Positive electrode material and preparation method thereof, positive plate and secondary battery

By using a non-layered lithium cobalt oxide compound coating layer doped with N elements and a layered lithium cobalt oxide matrix material doped with M elements in lithium cobalt oxide batteries, the structure of lithium cobalt oxide batteries at high voltage is solved. The low temperature and rate performance problems caused by instability have achieved higher electrochemical stability and performance improvement.

CN119153659APending Publication Date: 2024-12-17ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380429.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide batteries have deteriorated low temperature and rate performance due to unstable layered structure at high voltages, and traditional doping coating methods reduce material activity, affecting electrochemical performance.

Method used

Using a non-layered lithium cobalt oxide coating layer doped with N elements and a layered lithium cobalt oxide matrix material doped with M elements, the relative molar content of Li elements is controlled at 0.1≤a/b≤0.5, and by specific The firing and heating steps are used to prepare the cathode material to form a nanoscale cladding layer to improve the ionic conductivity and electrochemical stability of the material.

Benefits of technology

Effectively reduce the occurrence of lithium cobalt oxide holes and cracks at high voltages, improve low temperature and rate performance, while maintaining the electrochemical stability and cycling performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153659A_ABST
    Figure CN119153659A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive plate and a secondary battery. Comprising a base material and a coating layer coating the outer surface of the base material, the material of the coating layer is a non-layered lithium cobalt oxide doped with an N element, and the N element is at least one of Na, K, Ca and Mg; the matrix material is layered lithium cobalt oxide doped with an element M, and the element M is at least one of Al, Zr, Y and La; the relative molar content of Li in the coating layer is a, the relative molar content of Li in the matrix material is b, and a / b is larger than or equal to 0.1 and smaller than or equal to 0.5. Compared with the prior art, the concentration of Li on the surface layer of the lithium cobalt oxide is lower than that of the inner layer of the lithium cobalt oxide, so that the lithium removal rates of the inner layer and the surface layer of the lithium cobalt oxide are kept close, the generation of internal stress is reduced, and the generation of holes and cracks of the lithium cobalt oxide is reduced under the condition of high lithium removal and intercalation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, and a secondary battery. Background Art

[0002] In order to improve energy density, the charging voltage of electronic products using lithium cobalt oxide batteries is getting higher and higher. Commercial lithium cobalt oxide is mostly α-NaFeO 2 The layered structure will become unstable under the condition of deep lithium removal at high voltage. At present, the technology mostly uses the method of doping and coating to modify the high voltage stability of lithium cobalt oxide. However, doping and coating will reduce the activity of lithium cobalt oxide itself, especially the coating of inactive materials, which will affect the deintercalation of lithium ions on the surface of lithium cobalt oxide, causing the loss of lithium cobalt oxide activity and deteriorating the low temperature and rate performance of lithium cobalt oxide electronic products.

[0003] Bulk doping mainly uses F ions to partially replace oxygen for stabilizing the structure, reducing the redox reaction of oxygen anions. Although F doping can reduce the oxygen loss of lithium-rich positive electrode materials and improve the structural stability of the materials, due to the high electronegativity of F ions, there will also be a certain bonding attraction force on lithium ions in the bulk phase of the material, which will inhibit the diffusion and transport of lithium ions in the material; the surface coating layer can isolate the contact between the surface of the positive electrode material and the electrolyte, reduce adverse interfacial side reactions, stabilize the surface structure and composition of the material, and thus improve the electrochemical performance of the battery. Although there are many types of coating materials, the surface coating layer of commercial positive electrode materials is still mainly oxides. This type of traditional coating material can avoid direct contact between the electrolyte and the positive electrode material to a certain extent and improve the electrochemical stability of the material. However, since the coating layer material does not have electrochemical activity and the ion and electronic conductivity are limited, it is still impossible to maximize the optimal performance of the electrode material, which limits the improvement of the comprehensive performance of the material.

[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0005] One of the purposes of the present invention is to provide a positive electrode material to address the deficiencies in the prior art, so as to improve the problem that the current lithium cobalt oxide material causes holes and cracks in the lithium cobalt oxide when lithium ions are inserted and extracted, thereby causing the low temperature performance and rate performance of the battery to deteriorate.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A positive electrode material, comprising a base material and a coating layer coated on the outer surface of the base material, wherein the material of the coating layer is a non-layered lithium cobalt oxide compound doped with an N element, wherein the N element is at least one of Na, K, Ca, and Mg; and the base material is a layered lithium cobalt oxide doped with an M element, wherein the M element is Al, Zr, Y, L a At least one of;

[0008] The relative molar content of the Li element in the coating layer is a, the relative molar content of the Li element in the matrix material is b, and 0.1≤a / b≤0.5.

[0009] Preferably, in the XRD spectrum of the positive electrode material, the crystal plane diffraction peak (003) has a peak intensity of I 1 The strong peak and peak intensity are I 2 Weak peak, where 2≤I 1 / I 2 ≤10.

[0010] Preferably, the material chemical formula of the coating layer is Li x N y Co Z O, wherein the value of x is 0.1 to 0.7, the value of y is 0.01 to 0.02, and the value of z is 0.5 to 0.9. x N y Co z The mass ratio of O to matrix material is 1:100-500.

[0011] Preferably, the coating layer has a thickness of 1 to 30 nm.

[0012] The second object of the present invention is to provide a method for preparing a positive electrode material, comprising the following steps:

[0013] S1, mixing cobalt oxide, lithium salt and M-containing compound uniformly, and sintering in an air atmosphere to obtain M-doped lithium cobalt oxide;

[0014] S2, will (CH 3 COO 2 Co、C 3 H 7 Li and a compound containing N are dissolved in an organic solvent and heated in a closed reactor to react to obtain a lithium cobalt oxide doped with N;

[0015] S3, dissolving the N-doped lithium cobalt oxide compound prepared in S2 in an alcohol solvent, adding the M-doped lithium cobalt oxide prepared in S1, mixing evenly, filtering and drying to obtain the N-doped lithium cobalt oxide coated with the M-doped lithium cobalt oxide, and sintering in an air atmosphere to obtain the positive electrode material.

[0016] Preferably, in step S1, the sintering is performed in an air atmosphere at 680-750° C. for 4-8 hours, and then the temperature is raised to 1000-1200° C. and sintered for 18-22 hours.

[0017] Preferably, in step S2, the temperature of the heating reaction is 180-220° C., and the heating time is 15-20 h.

[0018] Preferably, in step S3, the sintering temperature is 300-500° C., and the sintering time is 22-26 hours.

[0019] The third object of the present invention is to provide a positive electrode sheet comprising the above-mentioned positive electrode material.

[0020] A fourth object of the present invention is to provide a secondary battery comprising the above-mentioned positive electrode sheet.

[0021] Compared with the prior art, the beneficial effect of the present invention is that the lithium cobalt oxide positive electrode material prepared by the present invention can take into account both low temperature performance and rate performance at high voltage. Among them, the concentration of Li in the surface layer of the lithium cobalt oxide in the present invention is lower than that in the inner layer of the lithium cobalt oxide, so that the lithium de-lithiation rate of the inner layer and the surface layer of the lithium cobalt oxide remains close, reducing the generation of internal stress, and reducing the occurrence of lithium cobalt oxide holes and cracks in the case of high lithium de-insertion. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the positive electrode material of Example 1 of the present invention.

[0023] Figure 2 This is the XRD diagram of the positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0025] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0026] The first aspect of the present invention is to provide a positive electrode material, which includes a base material and a coating layer coated on the outer surface of the base material, the material of the coating layer is a non-layered lithium cobalt oxide doped with N element, and the N element is at least one of Na, K, Ca, and Mg; the base material is a layered lithium cobalt oxide doped with M element, and the M element is at least one of Al, Zr, Y, and La.

[0027] The relative molar content of the Li element in the coating layer is a, the relative molar content of the Li element in the matrix material is b, and 0.1≤a / b≤0.5.

[0028] The N element is a low-valent metal element, and Li + The similar valence helps to maintain the charge balance on the surface of the material after doping, and at the same time, due to its low ion migration energy, it helps to enhance the ion conductivity of the material; the M element is an element with a valence of +3 or above, and Co 3+ With similar valence, Al, Zr, Y, and La all have the function of stabilizing the bulk phase structure. Al doping can inhibit the dissolution and phase change of cobalt, thereby improving the cycle stability. La, Y, and Zr have larger ionic radii, which play a supporting role, enhance the spacing of the C axis, and promote Li + migration speed.

[0029] Among them, the Li ion concentration in the coating layer is lower than that in the matrix material. This concentration difference can keep the lithium desorption rate of the outer layer material and the inner layer matrix material close, reduce the generation of internal stress, and under high voltage, lithium ions are highly deintercalated, effectively reducing the generation of lithium cobalt oxide pores and cracks, and improving the rate performance and low-temperature performance of lithium cobalt oxide positive electrode materials.

[0030] In some embodiments, in the XRD spectrum of the positive electrode material, the crystal plane diffraction peak (003) has a peak intensity of I 1 The strong peak and peak intensity are I 2 Weak peak, where 2≤I 1 / I 2 ≤10. The (003) peak in the XRD graph is split, indicating that a new phase is generated in the coating material. The new phase has higher electrochemical stability and can reduce side reactions on the surface. The chemical formula of the coating material is Li X N y Co Z O, this coating material is nano-scale particles.

[0031] In some embodiments, the coating material has a thickness of 1 to 30 nm. Specifically, it may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, and may include but is not limited to the values ​​exemplified above. If the coating layer is lower than this range, the coating layer is too thin, and it is easy to contact with the electrolyte, resulting in adverse interface side reactions, and changing the surface structure and composition of the material; if it is higher than this range, the coating layer is too thick, which is not conducive to the improvement of the battery rate and cycle performance; the coating layer with a thickness within this range has good lithium ion conduction characteristics, which is conducive to reducing the polarization resistance of lithium ions in the process of escaping and embedding on the surface of the positive electrode material, and improving the rate performance of the positive electrode material of the lithium battery of the present invention.

[0032] The second aspect of the present invention is to provide a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0033] S1, mixing cobalt oxide, lithium salt and M-containing compound uniformly, and firing in an air atmosphere to obtain M-doped lithium cobalt oxide;

[0034] S2, will (CH 3 COO 2 Co、C 3 H 7 Li and a compound containing N are dissolved in an organic solvent and heated in a closed reactor to react to obtain a lithium cobalt oxide compound doped with N;

[0035] S3, dissolving the N-doped lithium cobalt oxide compound prepared in S2 in an alcohol solvent, adding the M-doped lithium cobalt oxide prepared in S1, mixing evenly, filtering and drying to obtain the N-doped lithium cobalt oxide coated with the M-doped lithium cobalt oxide, and sintering in an air atmosphere to obtain the positive electrode material.

[0036] In some embodiments, in step S1, the material is sintered at 680-750°C in an air atmosphere for 4-8 hours, and then the temperature is raised to 1000-1200°C and sintered for 18-22 hours, wherein the air atmosphere temperature is preferably 700°C and the sintering time is 6 hours; during this process, lithium, oxygen, and M are adsorbed on the surface of the material to form lithium-rich nuclei on the surface, and the subsequent temperature is preferably raised to 1100°C and the sintering time is 20 hours, at which time the lithium-rich nuclei will continue to grow, and Li ions will gradually migrate from the surface to the interior of the oxide, and Co ions will continue to migrate to the near-surface area driven by the concentration gradient, and M ions will continue to migrate to the interior driven by the concentration, and oxygen anions enter the crystal lattice to provide power for the crystallization and growth of lithium cobalt oxide. Finally, under the influence of the chemical concentration gradient driving force and binding energy, M-doped lithium cobalt oxide will be generated.

[0037] In some embodiments, in step S2, the reactor temperature is 180-220°C, and the heating time is 15-20 hours. The reactor temperature is preferably 200°C, and the heating time is preferably 17 hours.

[0038] In some embodiments, in step S3, the air atmosphere temperature is 300-500°C, and the sintering time is 22-26 hours. At this temperature, it is low temperature sintering. Therefore, the N-doped lithium cobalt oxide prepared in step S2 will not be completely converted into a layered structure. On the side close to the matrix lithium cobalt oxide, under the action of thermal driving force, Co 2+ Oxidation to Co 3+ , and Li + and Co 3+ It will diffuse into the interior of the matrix lithium cobalt oxide, and finally obtain lithium cobalt oxide coated with lithium cobalt oxide compounds.

[0039] The third aspect of the present invention is to provide a positive electrode sheet, the positive electrode material mentioned above.

[0040] A fourth aspect of the present invention is to provide a secondary battery comprising the above-mentioned positive electrode sheet.

[0041] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0042] Example 1

[0043] A positive electrode material comprises a base material and a coating material coated on the outer surface of the base material, wherein the coating material is a lithium cobalt oxide doped with an N element, wherein the N element is Na; the base material is lithium cobalt oxide doped with an M element, wherein the M element is Al, and the ratio of the relative molar content a of Li in the coating material to the relative molar content b of Li in the base material is 0.34:1.

[0044] The preparation method of the positive electrode material is:

[0045] 1) Co 3 O 4 , Li 2 CO 3 and Al 2 O 3 According to the molar ratio of Li:Co being 1.05:1 and the molar ratio of Al:Co being within the range of 0.003 to 0.01, the materials are weighed and mixed evenly by a high-speed mixer, sintered at 700°C for 6 hours, and then sintered at 1100°C for 20 hours to obtain a lithium cobalt oxide semi-finished product;

[0046] 2) (CH 3 COO 2 Co、C 3 H 7 Li and CH 3 COONa is evenly distributed in tert-butyl alcohol, where (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.15, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.34 Na 0.01 Co 0.65 O nanoparticles;

[0047] 3) Li prepared in (2) 0.34 Na 0.01 Co 0.65 O is dissolved in ethanol solvent, and then the lithium cobalt oxide prepared in (1) is added into the ethanol solvent. 0.34 Na 0.01 Co 0.65 The mass ratio of O to lithium cobalt oxide was 1:300, and Li 0.34 Na 0.01 Co 0.65 O-coated lithium cobalt oxide. The material is then placed in an air atmosphere at 400°C and sintered at low temperature for 24 hours to finally obtain a positive electrode material of lithium cobalt oxide coated with a surface lithium cobalt oxide compound.

[0048] Preparation of positive electrode sheet: The positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) prepared above are fully stirred in a N-methyl methyl pyrrolidone solvent system at a mass ratio of 96:2.5:1.5. After stirring evenly, a positive electrode slurry is obtained, and the slurry is coated on Al foil, baked, rolled, and cut into strips to obtain a positive electrode sheet.

[0049] Preparation of negative electrode sheet: Graphite, conductive agent carbon nanotube, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 96.5:1.5:1:1. After being mixed evenly, the negative electrode slurry is coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.

[0050] Preparation of isolation membrane: Polyethylene (PE) polymer film is used as isolation membrane.

[0051] Preparation of electrolyte: The organic solvents are uniformly mixed according to the mass ratio to obtain an organic solvent mixture, the specific mass ratio is: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 20:28:2:30:20. Lithium salt LiPF is added to the organic solvent mixture. 6 , LiPF 6 The mass ratio of the mixed liquid to the organic solvent is 9:91, and after uniform mixing, the electrolyte of the lithium ion battery is obtained.

[0052] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, and wind them to obtain an electrode assembly. When folding the electrode sheets, pay attention to the separator to completely separate the positive and negative electrode sheets. Put the electrode assembly in a packaging shell, inject electrolyte into the packaging shell and package it, and finally obtain a lithium-ion battery.

[0053] Example 2

[0054] The difference from Example 1 is that in the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:200.

[0055] The rest is the same as in Example 1 and will not be described again here.

[0056] Example 3

[0057] The difference from Example 1 is that in the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:100.

[0058] The rest is the same as in Example 1 and will not be described again here.

[0059] Example 4

[0060] The difference from Example 1 is that the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:400.

[0061] The rest is the same as in Example 1 and will not be described again here.

[0062] Example 5

[0063] The difference from Example 1 is that the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:500.

[0064] The rest is the same as in Example 1 and will not be described again here.

[0065] Example 6

[0066] The difference from Example 1 is that in the preparation step 2), (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.10, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.24 Na 0.01 Co 0.75 O.

[0067] The rest is the same as in Example 1 and will not be described again here.

[0068] Example 7

[0069] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li was 1:1.20, and then heated at 200°C for 17h in a sealed autoclave to obtain Li 0.44 Na 0.01 Co 0.55 O.

[0070] The rest is the same as in Example 1 and will not be described again here.

[0071] Example 8

[0072] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.05, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.14 Na 0.01 Co 0.85 O.

[0073] The rest is the same as in Example 1 and will not be described again here.

[0074] Example 9

[0075] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.03, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.10 Na 0.01 Co 0.85 O.

[0076] The rest is the same as in Example 1 and will not be described again here.

[0077] Example 10

[0078] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.23, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.50 Na 0.01 Co 0.85 O.

[0079] The rest is the same as in Example 1 and will not be described again here.

[0080] Comparative Example 1

[0081] 1) Co 3 O 4 , Li 2 CO 3 and Al 2 O 3 According to the molar ratio of Li:Co being 1.05:1 and the molar ratio of Al:Co being within the range of 0.003 to 0.01, the materials are weighed and mixed evenly by a high-speed mixer, sintered at 700°C for 6 hours, and then sintered at 1100°C for 20 hours to obtain a lithium cobalt oxide semi-finished product;

[0082] 2) The prepared (1) and Al 2 O 3 After uniform mixing, the molar ratio of Al:Co was ensured to be 0.001, and then sintered at 1000°C for 24h to obtain an Al-coated lithium cobalt oxide positive electrode material.

[0083] Comparative Example 2

[0084] The difference from Example 1 is that in the preparation step 3), the sintering temperature is 800° C. and the sintering time is 24 h.

[0085] The rest is the same as in Example 1 and will not be described again here.

[0086] Comparative Example 3

[0087] The difference from Example 1 is that the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:50.

[0088] The rest is the same as in Example 1 and will not be described again here.

[0089] Comparative Example 4

[0090] The difference from Example 1 is that the preparation step 3) Li 0.34 Na 0.01 Co 0.65 The added mass ratio of O to lithium cobalt oxide is 1:600.

[0091] The rest is the same as in Example 1 and will not be described again here.

[0092] Comparative Example 5

[0093] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1.25, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.14 Na 0.01 Co 0.85 O; the rest is the same as in Example 1 and will not be described again here.

[0094] Comparative Example 6

[0095] The difference from Example 1 is that in the preparation step 2) (CH 3 COO 2 Co and C 3 H 7 The molar ratio of Li is 1:1, and then heated at 200℃ for 17h in a sealed autoclave to obtain Li 0.05 Na 0.01 Co 0.85 O.

[0096] The rest is the same as in Example 1 and will not be described again here.

[0097] The performance of the positive electrode materials obtained in the above Examples 1 to 10 and Comparative Examples 1 to 6 was tested.

[0098] The test results are shown in Table 1 below.

[0099] (1) Low temperature test

[0100] At room temperature, the soft-pack battery cell is charged to 4.53V at a constant current and constant voltage of 0.5C, with a cut-off current of 0.02C, and discharged to 3.0V at a constant current of 0.2C at room temperature (25°C). The room temperature discharge capacity is recorded as Cap1;

[0101] At room temperature, the soft-pack battery cell is charged to 4.53V at 0.5C constant current and constant voltage, with a cut-off current of 0.02C, and discharged to 3.0V at -10℃ at 0.2C constant current. The obtained -10℃ discharge capacity is recorded as Cap2;

[0102] The low temperature performance is the value of Cap2 / Cap1.

[0103] (2) Rate discharge test

[0104] At room temperature, the soft-pack battery cell is charged to 4.53V at a constant current and voltage of 0.5C, the cut-off current is 0.02C, and then discharged to 3.0V at a constant current of 0.2C. The room temperature discharge capacity is recorded as Cap3;

[0105] At room temperature, the soft-pack battery cell is charged to 4.53V at 0.5C constant current and constant voltage, with a cut-off current of 0.02C, and then discharged to 3.0V at 3.0C constant current. The room temperature discharge capacity is recorded as Cap4.

[0106] The rate performance is the value of Cap4 / Cap3.

[0107] (3) Cycle performance test: The soft-pack battery cell is placed in an environment of 45°C, charged at a constant current and constant voltage of 3C to 4.53V, the cut-off current is 0.05C, and discharged at a constant current of 0.7C to 3.0V. This step of charge and discharge is recorded as one cycle. This cycle is repeated until the capacity retention rate of the battery cell is less than 80%. The battery cell is stopped from being tested and the cycle number of this battery cell is recorded.

[0108] (4) Coating layer thickness: The prepared positive electrode material was tested by TEM to obtain the coating layer thickness.

[0109] The parameters and test results of the embodiment are shown in Table 1 below.

[0110] Table 1

[0111]

[0112]

[0113] “ / ” in the table means that the feature is not available.

[0114] As shown in Table 1, the positive electrode material coated and doped in the present invention is better than the conventional one using Al 2 O 3The coated positive electrode material has better low temperature performance, rate performance and cycle performance. From Examples 1-5 and Comparative Examples 3-4, it can be seen that Li x Na y Co z The mass ratio of O to the base material lithium cobalt oxide affects the coating thickness and electrical properties of the positive electrode material. When the mass ratio provided by the present invention is used, the battery has better low temperature performance, rate performance and cycle performance. It can be seen from Examples 1, 6-10 and Comparative Examples 5-6 that when the ratio between the relative molar content a of the Li element in the coating layer and the relative molar content b of the Li element in the base material is 0.1≤a / b≤0.5, the battery has better low temperature performance, rate performance and cycle performance.

[0115] In summary, the lithium cobalt oxide positive electrode material prepared by the present invention can take into account both low temperature performance and rate performance at high voltage. Among them, the concentration of Li in the surface layer of the lithium cobalt oxide in the present invention is lower than that in the inner layer of the lithium cobalt oxide, so that the lithium de-lithiation rate of the inner layer and the surface layer of the lithium cobalt oxide remains close, reducing the generation of internal stress, and reducing the occurrence of lithium cobalt oxide holes and cracks in the case of high lithium deintercalation. At the same time, when preparing the positive electrode material, the present invention adopts low temperature sintering in the last sintering step, so that the surface of the prepared positive electrode material is a non-layered structure of lithium cobalt oxide compounds, and the inner layer is a layered structure.

[0116] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A positive electrode material, It is characterized in that It comprises a base material and a coating layer coated on the outer surface of the base material, wherein the material of the coating layer is a non-layered lithium cobalt oxide compound doped with an N element, wherein the N element is at least one of Na, K, Ca, and Mg; the base material is a layered lithium cobalt oxide doped with an M element, wherein the M element is at least one of Al, Zr, Y, and La; The relative molar content of the Li element in the coating layer is a, the relative molar content of the Li element in the matrix material is b, and 0.1≤a / b≤0.

5.

2. The positive electrode material according to claim 1, It is characterized in that In the XRD spectrum of the positive electrode material, the crystal plane diffraction peak (003) has a peak intensity of I 1 The strong peak and peak intensity are I 2 Weak peak, where 2≤I 1 / I 2 ≤10.

3. The positive electrode material according to claim 1, It is characterized in that The material chemical formula of the coating layer is Li X N y Co Z O, wherein the value of x is 0.1 to 0.7, the value of y is 0.01 to 0.02, and the value of z is 0.5 to 0.

9. x N y Co z The mass ratio of O to the matrix material is 1:100-500.

4. The positive electrode material according to claim 1, It is characterized in that The coating layer has a thickness of 1 to 30 nm.

5. A method for preparing the positive electrode material according to any one of claims 1 to 4, It is characterized in that The following steps are involved: S1, mixing cobalt oxide, lithium salt and M-containing compound uniformly, and sintering in an air atmosphere to obtain M-doped lithium cobalt oxide; S2, will (CH 3 COO 2 Co、C 3 H 7 Li and a compound containing N are dissolved in an organic solvent and heated in a closed reactor to react to obtain a lithium cobalt oxide compound doped with N; S3, dissolving the N-doped lithium cobalt oxide compound prepared in S2 in an alcohol solvent, adding the M-doped lithium cobalt oxide prepared in S1, mixing evenly, filtering and drying to obtain the N-doped lithium cobalt oxide coated with the M-doped lithium cobalt oxide, and sintering in an air atmosphere to obtain the positive electrode material.

6. The method for preparing the positive electrode material according to claim 5, It is characterized in that In step S1, the sintering is carried out in an air atmosphere at 680-750° C. for 4-8 hours, and then the temperature is raised to 1000-1200° C. for 18-22 hours.

7. The method for preparing the positive electrode material according to claim 5, It is characterized in that In step S2, the temperature of the heating reaction is 180-220° C., and the heating time is 15-20 hours.

8. The method for preparing the positive electrode material according to claim 5, It is characterized in that In step S3, the sintering temperature is 300-500° C., and the sintering time is 22-26 hours.

9. A positive electrode sheet, It is characterized in that The positive electrode material comprises the positive electrode material according to any one of claims 1 to 4.

10. A secondary battery, It is characterized in that Including the positive electrode sheet as described in claim 9.